Transdiagnostic patient experiences of dialectical behavioural therapy: a systematic review and metasynthesis - Hall, Abigail; Gregg, Lynsey; O’Ceallaigh, Brian; Wittkowski, Anja (Frontiers in Psychiatry, 2025)
BackgroundDialectical Behaviour Therapy (DBT) combines cognitive-behavioural techniques and mindfulness practices to more skilfully regulate intense emotions and navigate interpersonal issues. While traditional DBT (skills group, individual therapy and crisis support) is well-studied in clinical populations, particularly for emotion regulation in conditions like borderline personality disorder or emotionally unstable personality disorder, recent research has explored alternative formats, such as skills-only groups. Although quantitative studies report positive outcomes (e.g., reduced self-injury and suicidality), less is known about patient experiences, which are crucial for developing effective interventions. This systematic review explored patient experiences of DBT skills groups across mental health conditions and age groups, considering the processes patients perceived as contributing to therapeutic change and outcomes.MethodA systematic search was conducted across five databases following PRISMA guidelines, using search terms related to DBT and patient experience. Peer-reviewed papers employing qualitative or mixed-methods were included. Thematic synthesis was used for analysis.ResultsThirty-two papers were eligible for inclusion. Three main themes were generated: 1) the challenging road to DBT, 2) the difficult journey through DBT, and 3) patients’ path for the future. Theme two contained three sub-themes (from theory to practice, transformative relationships - self and others, scaffolding and supporting change) and theme three included two sub-themes (therapeutic gains, future directions).ConclusionsFindings highlight the importance of pre-treatment and in-treatment experiences alongside relational factors like safety and validation and practical skill application. Key processes, including peer support and changed perspectives, shape therapeutic outcomes. Recommendations include flexible delivery formats and aligning patient preferences with intervention to maximise gains.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/login, identifier PROSPERO (CRD42024604496).